Implementasi Model Pembelajaran Think Pair Share (TPS) Berbasis Lesson Study untuk Meningkatkan Aktivitas Belajar dan Keterampilan Metakognitif Mahasiswa pada Matakuliah Pengembangan Kurikulum IPA SMP - R. Didi Kuswara; Suci Ferdiana; Tismi Dipalaya; Illiyatus Sholihah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
21st century learning is learning oriented to the formation of students who have the skills or skills needed in living the 21st century life, such as being able to communicate and collaborate well and have metacognitive skills. Improving the quality of education is important, one of which is improving the learning process in the classroom by applying learning models that can develop students' abilities. One of them is by applying the Think Pair Share (TPS) cooperative learning model. The purpose of this study was to improve learning activities and metacognitive skills of Biology Education students in the Science Curriculum Development course at SMP Negeri Malang State University. This type of research is Classroom Action Research based on Lesson Study (PTK-LS). The research approach used is descriptive qualitative. The results showed that: 1) the percentage level of the implementation of the Think Pair Share (TPS) cooperative learning model was very good, namely 80%; 2) student learning activities in semester VII have increased by 2.01%; and 3) the metacognitive skills of seventh semester students have increased by an average of 2.26. The conclusion is that the Think Pair Share (TPS) cooperative learning model can improve student learning activities and metacognitive skills.